Cerebrovascular Reactivity Measures Are Associated With Post-traumatic Headache Severity in Chronic TBI; A Retrospective Analysis - Amyot, Franck; Lynch, Cillian E.; Ollinger, John; Werner, J. Kent; Silverman, E.; Moore, Carol; Davis, Cora; Turtzo, L. Christine; Diaz-Arrastia, Ramon; Kenney, Kimbra (Frontiers in Physiology, 2021)
Objective: To characterize the relationship between persistent post-traumatic headache (pPTH) and traumatic cerebrovascular injury (TCVI) in chronic traumatic brain injury (TBI). Cerebrovascular reactivity (CVR), a functional measure of the cerebral microvasculature and endothelial cell function, is altered in individuals with both chronic TBI and migraine headache disorder.1, 2 The pathophysiology of both pPTH and migraine are believed to be associated with chronic microvascular dysfunction. We therefore hypothesize that TCVI may contribute to the underlying mechanism(s) of pPTH that are migraine-like. Method: 22 moderate/severe TBI participants in the chronic stage (>6 months) underwent anatomic and functional magnetic resonance imaging (fMRI) scanning with hypercapnia gas challenge to measure CVR as well as the change in CVR (ΔCVR) after single-dose treatment of a specific phosphodiesterase-5 (PDE-5) inhibitor, sildenafil, that potentiates vasodilation in response to hypercapnia in impaired endothelial cells. CVR and ΔCVR measures of each participant were compared with the individual’s pPTH severity measured by the headache impact test-6 (HIT-6) survey. Results: There was a moderate correlation between HIT-6 and both CVR and ΔCVR scores (Spearman’s correlation =-0.50 (p=0.018) and=0.46 (p=0.03), respectively), indicating that a higher headache burden is associated with decreased endothelial function in our chronic TBI population. Conclusion: There is a correlation between PTH and CVR in chronic moderate-severe TBI. This relationship suggests that chronic TCVI may underlie the pathobiology of pPTH. Further, our results suggest that novel treatment strategies that target endothelial function and vascular health may be beneficial in refractory pPTH.